2019
DOI: 10.2337/cd18-0063
|View full text |Cite
|
Sign up to set email alerts
|

Practical Insights Into Improving Adherence to Metformin Therapy in Patients With Type 2 Diabetes

Abstract: Metformin is a biguanide that is highly effective at lowering both basal and prandial glucose levels by reducing hepatic glucose production, increas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…These findings suggest that if patients are supported to continue taking their metformin beyond 3 months, they are likely to remain on it successfully at least for 1 year. A number of strategies, including enhanced patient‐provider communication, e‐Health interventions, and using extended‐release formulations have been shown to improve adherence to metformin 29 …”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that if patients are supported to continue taking their metformin beyond 3 months, they are likely to remain on it successfully at least for 1 year. A number of strategies, including enhanced patient‐provider communication, e‐Health interventions, and using extended‐release formulations have been shown to improve adherence to metformin 29 …”
Section: Discussionmentioning
confidence: 99%
“…Strategies to optimise adherence to metformin will be needed, especially given the asymptomatic nature of non-diabetic hyperglycaemia. 102 Some trials in progress in populations with non-diabetic hyperglycaemia, described above, are using the XR formulation of metformin, which may support better adherence to therapy than the immediate-release formulation, based on clinical experience in people with type 2 diabetes. 103…”
Section: Adherencementioning
confidence: 99%
“…Metformin (1500–3000 mg/day for 6 months) is recognized as a well-tolerated anti-diabetic drug [78]. Importantly, several studies revealed that metformin decreases the risk of many cancers including hepatocellular carcinoma and prostate cancer [79,80].…”
Section: The Synergistic Effect Of Curcumin Combination Chemotherapymentioning
confidence: 99%